The Influence Of Facilities And Prices On Tourist Satisfaction At Pantjoran PIK, North Jakarta - Yonnata Yonnata (Green Publisher Indonesia, 2024)
This study investigates the influence of facilities and prices on tourist satisfaction at Pantjoran PIK, North Jakarta. The research employed a quantitative approach with 115 respondents who had visited the destination. Using multiple linear regression analysis, the results show that both facilities and prices have a significant and positive effect on tourist satisfaction. Specifically, well-maintained facilities, such as cleanliness, parking availability, and comfort, enhance the overall experience of visitors. Similarly, reasonable prices that align with the quality of services provided also contribute to higher satisfaction levels. The findings suggest that improving facilities and maintaining competitive pricing can lead to increased tourist satisfaction and loyalty. Future research may explore additional factors influencing visitor satisfaction.